Lower Jurassic conodonts from the Inuyama area of Japan: implications for conodont extinction - Du, Yixing; Onoue, Tetsuji; Tomimatsu, Yuki; Wu, Qiangwang; Rigo, Manuel (Frontiers in Ecology and Evolution, 2023)
It is generally accepted that conodonts went extinct at the end of the Triassic, but younger conodont fossils have been reported, and it is becoming clear that conodont extinction occurred asynchronously across different regions. Although some reports of post-Triassic conodonts have been disproven, truly Lower Jurassic conodonts have been found in the Buda area of Hungary and the Inuyama area of Japan. Here, we report the discovery of more conodonts Misikella posthernsteini above the first occurrence of the Jurassic radiolarian Pantanellium tanuense from the Kastuyama section, Inuyama area, reaffirming the authenticity of the Lower Jurassic conodonts. The conodonts survived into the Jurassic in the Inuyama area might be due to their remote locations relative to the Central Atlantic Magmatic Province, which buffered them from hypoxia and ocean acidification. Although conodont survived into the Lower Jurassic, it failed to recover and quickly went extinct in post-extinction ecosystems. The “dead clades walking” (DCWs) of conodont may have been due to protracted ocean acidification in the earliest Jurassic. Food scarcity and competition with other organisms may have led to the eventual extinction of conodonts.